Glutamate-dependent ectodomain shedding of neuregulin-1 type II precursors in rat forebrain neurons. - Yuriko Iwakura; Ran Wang; Naoko Inamura; Kazuaki Araki; Shigeki Higashiyama; Nobuyuki Takei; Hiroyuki Nawa (PLoS ONE, 2017)
The neurotrophic factor neuregulin 1 (NRG1) regulates neuronal development, glial differentiation, and excitatory synapse maturation. NRG1 is synthesized as a membrane-anchored precursor and is then liberated by proteolytic processing or exocytosis. Mature NRG1 then binds to its receptors expressed by neighboring neurons or glial cells. However, the molecular mechanisms that govern this process in the nervous system are not defined in detail. Here we prepared neuron-enriched and glia-enriched cultures from embryonic rat neocortex to investigate the role of neurotransmitters that regulate the liberation/release of NRG1 from the membrane of neurons or glial cells. Using a two-site enzyme immunoassay to detect soluble NRG1, we show that, of various neurotransmitters, glutamate was the most potent inducer of NRG1 release in neuron-enriched cultures. NRG1 release in glia-enriched cultures was relatively limited. Furthermore, among glutamate receptor agonists, N-Methyl-D-Aspartate (NMDA) and kainate (KA), but not AMPA or tACPD, mimicked the effects of glutamate. Similar findings were acquired from analysis of the hippocampus of rats with KA-induced seizures. To evaluate the contribution of members of a disintegrin and metalloproteinase (ADAM) families to NRG1 release, we transfected primary cultures of neurons with cDNA vectors encoding NRG1 types I, II, or III precursors, each tagged with the alkaline phosphatase reporter. Analysis of alkaline phosphatase activity revealed that the NRG1 type II precursor was subjected to tumor necrosis factor-α-converting enzyme (TACE) / a Disintegrin And Metalloproteinase 17 (ADAM17) -dependent ectodomain shedding in a protein kinase C-dependent manner. These results suggest that glutamatergic neurotransmission positively regulates the ectodomain shedding of NRG1 type II precursors and liberates the active NRG1 domain in an activity-dependent manner.